Characterization of Enterobacter cloacae isolated from street foods - Yuli, Haryani; Robin, Tunung; Chai, Lay Ching; Lee, Hai Yen; Tang, Sui Yan; Radu, Son (Universiti Putra Malaysia Press, 2008)
A total of 78 samples comprising different types of street foods, sold in different locations in Malaysia, were examined for the presence of Enterobacter cloacae. E. cloacae contamination was recorded in 9% of the samples examined. Tests for susceptibility to 12 different antibiotics showed that all were resistant to six or more antibiotics, but susceptible to chloramphenicol and gentamicin. Plasmids of four different sizes were detected from the three plasmid positive isolates. RAPD analysis using four primers yielded completely different banding patterns for all E. cloacae studied. In Malaysia, no published information on street foods in the epidemiological investigation of E. cloacae related disease is available. However, their occurrences have provided compelling evidence that the risk of disease transmission caused by E. cloacae through street foods is moderate.